KOMUNIKASI DAN PENDIDIKAN POLITIK ULAMA DAYAH ACEH DALAM PILKADA 2024 DI KABUPATEN BIREUEN - Arahman, Zulfikar; Fahmi, Zulfan (STIT Ibnu Rusyd Tanah Grogot, 2025)
Political Communication of Aceh’s Dayah Ulama in the 2024 Regional Elections in Bireuen District. This study examines the role and political communication strategies of dayah ulama in Bireuen District during the 2024 Regional Elections (Pilkada). Dayah ulama hold a strategic position as influential religious figures in shaping public opinion and determining the political support of the community. The study aims to understand the communication patterns employed by dayah ulama in conveying political messages, the main issues they advocate, and their influence on voter behavior. Using qualitative research with a phenomenological approach, data were collected through observation, in-depth interviews, and documentation to capture the phenomenon comprehensively. The findings reveal that dayah ulama prioritize religious values, justice, and social welfare in their political messages and education. The communication strategies implemented include the use of religious study forums (pengajian), sermons (khutbah), and social media to expand their audience reach. The role of dayah ulama in the 2024 Pilkada extends beyond merely supporting specific candidates; they also act as guardians of political morality within the community. This study provides insights into the relationship between religion and politics as well as the relevance of dayah ulama in local political dynamics.